Sensory-related Attributes of Raw and Cooked Meat of Culled Saanen Goat Marinated in Ginger and Pineapple Juices - A. A. Putra; S. Wattanachant; C. Wattanachant (Faculty of Animal Science, Bogor Agricultural University, 2019)
The effects of ginger and pineapple juices on pH, color (L*, a*, b*), thiobarbituric acid reactive substances (TBARS), sensory intensity, and sensory preference of culled goat meat were determined.Completely randomized design (CRD) and randomized completely block design (RCBD) were applied for physicochemical attributes and sensory profiles, respectively. In raw condition, the pH of ginger-marinated sample was higher than that of pineapple-marinated sample. The increased trend in pH was found in the ginger-marinated and control-marinated samples, while the decreased trend was found in pineapple-marinated sample. A better redness stability of ginger-marinated sample was observed during the storage. Both plant juices had significant effects on controlling the malonaldehyde (MDA) formation. Ginger-marinated sample exhibited a brighter red color, less gamey odor, stronger marinated odor, and higher preference. In cooked samples, increasing pH but still with similar trend as in all raw samples was recorded. L* and b* of all samples were decreased on the fifth day of storage, while a* of ginger-treated sample was immensely elevated. Marinated juices were significant on retarding MDA formation along with less browning color and gamey aroma intensities. Reddish-brown color and stronger marinated odor resulted in high preferences on ginger-marinated sample. Less brown color in pineapple-marinated sample contributes to lower color and overall acceptances. In conclusion, ginger juice had a significant effect on covering the gamey flavor and showed positive effect on other sensory-supported attributes.